Meningkatkan Semangat Pemulihan Penyalahgunaan Narkoba Melalui kelas Motivasi Dan Rekreasional Sport - Simson Simanjuntak; Hairani Siregar (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Efforts to prevent drug trafficking and abuse continue to be carried out. One of them is the establishment of a drug rehabilitation center as a form of response to the alleviation of drug abuse. IPWL Nazar Foundation as a drug rehabilitation center aims to treat and cure drug addicts. However, not infrequently there are still former addicts who return to using drugs (relapse) so that he is rehabilitated again, one of which is a client with the initials HG. So that an alternative is needed in solving the problem. In this case, the process of providing assistance is carried out by providing motivational classes and recreational sports activities using the casework method. The achievement of the method used in overcoming the client's problems is that there are significant positive developments and changes in the client, where he is able to control himself and mature himself so that he can overcome his potential recurrence.